Do you see what I see? A character analysis of health risk behaviors in television shows popular with Black adolescents in the US. Issue 4 (2nd October 2018) - Bleakley, Amy; Ellithorpe, Morgan E.; Prince, Lisa; Hennessy, Michael; Khurana, Atika; Jamieson, Patrick E.; Weitz, Ilana
ABSTRACT: Adolescents spend many hours per day watching television, and there are racial differences in time spent watching television and in show preferences. Prior research suggests there are also differential associations in how exposure to media content affects adolescent behavior. This study examines the demographic representation of main characters and health risk behaviors (i.e., sex, alcohol use, violence, bullying, and their combinations) portrayed in television content popular with Black and non-Black adolescents. A content analysis of television show characters ( n  = 377) from the 2014–2015 season was conducted on shows popular with 14–17-year old adolescent audiences in the United States. Group popularity was determined by Nielsen ratings segmented by Black and non-Black (primarily White) adolescents. Results suggest that character representation varies by whether shows were popular with Blacks or others, and that risk portrayals are common in all popular content with few group differences. Implications for adolescent behavior are discussed.